Means of linguistic expression of the concept of «man» (the novel V. Shklyara «Zalishenets») (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The paper describes the development of cognitive linguistics, lingvokontseptologii, revealed the term «concept», the concept of «man», the basic conceptual aspects and verbalizatory this concept.
Keywords: verbalizatory; concept; conceptual aspect; lingvokontseptologiya